2016
DOI: 10.1007/s12576-016-0458-z
|View full text |Cite
|
Sign up to set email alerts
|

Does consumption of an aqueous extract of Hibscus sabdariffa affect renal function in subjects with mild to moderate hypertension?

Abstract: Hibiscus sabdariffa (HS) has been traditionally used as a herbal medicine in Nigeria mainly because of its antihypertensive action. In view of the recent increase in the prevalence of renal failure, we have investigated the effect of HS consumption on renal function in Nigerians with mild to moderate hypertension. A total of 78 newly diagnosed but untreated subjects with mild to moderate hypertension attending the medical outpatients unit of Enugu State University Teaching Hospital (Enugu, Nigeria) were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Creatinine level in the serum is proportional to the rate at which it is excreted (Eteng et al, 2009). The nephroprotective effect of H. sabdariffa observed in this study may be attributable to the action of anthocyanins a phytochemical component that has been previously reported in H. sabdariffa (Ines et al, 2014), in increasing the GFR via inhibition of angiotensin II production (Nwachukwu et al, 2016) . Angiotensin II adversely changes the renal perfusion and increases oxidative stress through inflammatory and thrombotic effects and it was considered to play a pivotal role in chronic kidney disease (CKD) progression (Wang et al, 2013).…”
Section: Discussionsupporting
confidence: 74%
“…Creatinine level in the serum is proportional to the rate at which it is excreted (Eteng et al, 2009). The nephroprotective effect of H. sabdariffa observed in this study may be attributable to the action of anthocyanins a phytochemical component that has been previously reported in H. sabdariffa (Ines et al, 2014), in increasing the GFR via inhibition of angiotensin II production (Nwachukwu et al, 2016) . Angiotensin II adversely changes the renal perfusion and increases oxidative stress through inflammatory and thrombotic effects and it was considered to play a pivotal role in chronic kidney disease (CKD) progression (Wang et al, 2013).…”
Section: Discussionsupporting
confidence: 74%
“…Oxidative stress and inflammation are known to be constant features in CKD, and this may be the basis of the ensuing increase in BP and other consequences . The mechanisms by which HS aqueous extract and anthocyanins abate the studied parameters of CKD may include their antihypertensive action, and the reduction of inflammatory cytokines and oxidative stress markers that were raised by adenine feeding. Oxidative stress is known to cause glomerular sclerosis, tubular injury, albuminuria and gradual renal dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the hypotensive activity was observed also in humans (Nwachukwu et al, 2015). In particular, clinical studies demonstrated that the administration of H. sabdariffa extracts to hypertensive patients reduces BP (Nwachukwu et al, 2015;Herrera-Arellano et al, 2004;Herrera-Arellano et al, 2007;McKay et al, 2010;Nwachukwu et al, 2017).…”
Section: Hibiscus Sabdariffa Lmentioning
confidence: 95%
“…In addition, the polyphenol content influences the course of obesity (Rodriguez-Perez et al, 2017). Moreover, Hibiscus sabdariffa consumption was reported to improve renal function in a population study of Nigerians with mild to moderate hypertension (Nwachukwu et al, 2017).…”
Section: Hibiscus Sabdariffa Lmentioning
confidence: 99%